2000
DOI: 10.1007/s004170000138
|View full text |Cite
|
Sign up to set email alerts
|

MHC expression in fragment and full-thickness allogeneic embryonic retinal transplants

Abstract: The findings suggest that host immune response against fragmented and intact neuroretinal grafts is different, indicating tissue integrity as one factor affecting graft-host immune interactions. The absence of immune response in full-thickness grafts is encouraging and important in the struggle to find therapies for retinal degenerative disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
14
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 30 publications
4
14
0
Order By: Relevance
“…Further, we have previously found MHC up-regulation in allogeneic fragmented transplanted cells, but not in fullthickness counterparts (Ghosh et al 2000). Taken together our present results and previous studies suggest that retinal elements in the donor tissue up-regulate MHC molecules in response to fragmentation trauma, and that the ensuing inflammation is a rejection caused by the immunological disparity between donor and host.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Further, we have previously found MHC up-regulation in allogeneic fragmented transplanted cells, but not in fullthickness counterparts (Ghosh et al 2000). Taken together our present results and previous studies suggest that retinal elements in the donor tissue up-regulate MHC molecules in response to fragmentation trauma, and that the ensuing inflammation is a rejection caused by the immunological disparity between donor and host.…”
Section: Discussionsupporting
confidence: 84%
“…Studies on donor tissue characteristics in relation to graft survival include donor-age, inclusion of antigen presenting cells and blood vessels, but as yet, tissue-integrity has not been extensively explored (Aramant et al, 1988;Marion et al, 1990). We have previously reported that allogeneic fragmented grafts (rabbit-to-rabbit) induce up-regulation of major histocompatibility complex (MHC) class I and II molecules in the graft and host while their full-thickness counterparts do not show such upregulation (Ghosh et al, 2000). We have further reported that full-thickness donor tissue, at least in the short-term, can survive xenogeneic transplantation between discordant species (rat-to-rabbit) without immunosuppression (Rauer and Ghosh, 2001).…”
mentioning
confidence: 99%
“…If we add to this the possibility of enhanced exposure of conventional transplantation and retina-restricted antigens in fragmented donor tissue, acute rejection of such grafts is hardly surprising [6]. In accordance with our earlier reports on transplantation to the SRS [11,16], donor tissue integrity appears to be an important factor for survival of neuroretinal grafts also in non-immune privileged sites.…”
Section: Discussionsupporting
confidence: 78%
“…Primary antibodies directed against microtubule-associated protein 2 (MAP2, monoclonal, mouse IgG1 isotype, 1:200 dilution, Sigma, St. Louis, MO, USA) and glial fibrillary acidic protein (GFAP, monoclonal, 1:1000 dilution, Chemicon International, Temecula, CA, USA) were used to detect graft-related neurons, and glial cells, respectively [14,15]. To identify inflammatory cells, a monoclonal antibody raised against rabbit major histocompatibility complex (MHC) class II was used (Mab 45-3, 1:200 dilution, Spring Valley Laboratories, Woodbine, Md., USA) [16]. Labeled sections were kept at room temperature for 20 min and then rinsed three times for 5 min in a solution of PBS and 0.25% Triton X-100 at 7.2 pH.…”
Section: Tissue Preparationmentioning
confidence: 99%
“…HLA-ABC molecules are expressed on the RPE constitutively. HLA-ABC molecules and HLA-DR molecule are upregulated significantly after being stimulated with proinflammatory cytokines such as IFN-γ and TNF-α [12]. The ICAM-1 molecule is the ligand for the LFA-1 on T cells.…”
Section: Discussionmentioning
confidence: 99%